Pemanfaatan Sludge Ash Pond PT. Cirebon Electrical Power (CEP) sebagai Bahan Bakar Alternatif - Agik Dwika Putra; Ilham Satria Raditya Putra; Rochim Bakti Cahyono (Eksergi, 2023)
As one of the power plants that uses coal as an energy source, PT Cirebon Electric Power (PT CEP) is committed to addressing waste problems with the 3R principle. Sludge ash ponds which is waste of the process production has the potential for alternative fuel. This study aims to evaluate the utilization of sludge ash ponds with the main target parameter in the form of calorific value. Based on proximate analysis, sludge pond ash only had a low heating value, around 210 kcal/kg, thus unbeneficial to be used as fuel directly. In order to make efficient utilization, a pyrolysis process was carried out to increase the existing heating value and was obtained at 700 – 870 kcal/kg. Generally, the standard of alternative fuel had minimum heating value of 4500 kcal/kg, therefore the blending process was carried out based on the fuel availability in the industrial site. The results of blending using coal showed that the high heating value of mixed briquette product was achieved at elevated more coal content used. By paying attention to the standard heating value, the ratio composition of ash pond to coal, 20/80 satisfy for utilization, where the heating value was around 4600 kcal/kg. The blending proses using pyrolysis char of ash pond showed un significant effect on the increasing of heating value, for example in a 40/60 ratio, the difference between the two types materials was only 210 kcal/kg. Therefore, pyrolysis pretreatment of sludge ash pond had unsignificant impact compared to the energy expended to run the process